An in vitro Blood-brain barrier model combining shear stress and endothelial cell/astrocyte co-culture - Takeshita, Yukio (2014)
BACKGROUND: In vitro blood-brain barrier (BBB) models can be useful for understanding leukocyte-endothelial interactions at this unique vascular-tissue interface. Desirable features of such a model include shear stress, non-transformed cells and co-cultures of brain microvascular endothelial cells with astrocytes. Recovery of transmigrated leukocytes for further analysis is also appealing. NEW METHODS: We report an in vitro BBB model for leukocyte transmigration incorporating shear stress with co-culture of conditionally immortalized human endothelial cell line (hBMVEC) and human astrocyte cell line (hAST). Transmigrated leukocytes can be recovered for comparison with input and non-transmigrated cells. RESULT: hBMVEC and hAST exhibited physiological and morphological BBB properties when cocultured back-to-back on membranes. In particular, astrocyte processes protruded through 3μm membrane pores, terminating in close proximity to the hBMVEC with a morphology reminiscent of end-feet. Co-culture with hAST also decreased the permeability of hBMVEC. In our model, astrocytes promoted transendothelial leukocyte transmigration. COMPARISON WITH EXISTING METHOD: This model offers the opportunity to evaluate whether BBB properties and leukocyte transmigration across cytokine-activated hBMVEC are influenced by human astrocytes. CONCLUSIONS: We present a model for leukocyte transmigration incorporating shear stress with coculture of hBMVEC and hAST. We demonstrated that hAST promoted leukocyte transmigration and also increased certain barrier functions of hBMVEC. This model provides reproducible assays for leukocyte transmigration with robust results, which will enable further defining the relationships among leukocytes and the cellular elements of the BBB.